Pembangunan Identitas Keagamaan dalam Ruang Digital (Studi Kasus tentang Kristen Cabang Muhammadiyah di Media Sosial) - Abdul Rahman Matondang; Tuti Restilia Dalimunthe; Maryam Khodimatullah (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2023)
This research aims to understand the development of the religious identity of Kristen Cabang Muhammadiyah on social media. The method used is a qualitative approach with Twitter social media analysis. The research findings indicate that social media plays a significant role in the construction of religious identity in the digital era. Through social media, individuals and religious groups can interact, share information, and strengthen their religious identity. Strategies for developing religious identity on social media include disseminating relevant content, building online communities, collaborating with religious figures, promoting engagement in offline activities, and strengthening solidarity among religious followers. Social media content analysis shows that the response to Kristen Cabang Muhammadiyah is still limited and does not indicate a sustained discussion trend. The impact of social media activities on religious identity includes increasing awareness, expanding message reach, building communities, and enhancing public understanding. This research provides valuable insights for understanding the dynamics of religious identity in the digital space and the relationship between religions in Indonesia and the influence of social media on them.